The Eternal Return to the Sources of Modern Military Strategy: Rome and Its Battles - Florin Pintescu (Codrul Cosminului)
Rome was and remains to this day, in terms of military history, the inspiration for the world's great strategists. Thus, the Kingship and the early period of the Republic include thirteen wars, the first part of the 4th century BC involves the Eternal City in seven military conflicts, the long conflict with the Samnites records nine wars, and the completion of the conquest of Italy by the Romans involves another three wars. Rome's expansion outside Italy is mainly through the first two Punic Wars, the wars in the Iberian Peninsula, the Illyrian Wars, the two wars with the Celts (Boii), the two wars fought with Philip V of Macedon, and the war fought with Antiochus III Megas of Syria. These military events, which shaped the fate of the ancient world in Europe, northern Africa, and much of Asia, are described based on ancient sources and the research of modern historians, by an author from Romania.